Stimulated Human Umbilical Cord Mesenchymal Stem Cells Enhance the Osteogenesis and Cranial Bone Regeneration through IL-32 Mediated P38 Signaling Pathway - Xiaru Zhang; Ying Zheng; Gang Wang; Yuanlin Liu; Yang Wang; Xueyi Jiang; Yueqing Liang; Xinfeng Zhao; Ping Li; Yi Zhang (Hindawi Limited, 2024)
Objective. Our previous study found that it could significantly increase the expression of IL32 after stimulating the human umbilical cord mesenchymal stem cells (S-HuMSCs). However, its role on the osteogenesis and cranial bone regeneration is still largely unknown. Here, we investigated the possible mechanism of this effect. Material and Methods. A series of experiments, including single-cell sequencing, flow cytometry, quantitative real-time polymerase chain reaction, and western blotting, were carried out to evaluate the characteristic and adipogenic-osteogenic differentiation potential of IL-32 overexpression HuMSCs (IL-32highHuMSCs) through mediating the P38 signaling pathway. Moreover, a rat skull bone defect model was established and treated by directly injecting the IL-32highHuMSCs to conduct its role on the cranial bone regeneration. Results. In total, it found that compared to HuMSCs, IL32 was significantly increased and promoted the osteogenic differentiation (lower expressions of PPARγ, Adiponectin, and C/EBPα, and increased expressions of RUNX2, ALP, BMP2, OPN, SP7, OCN, and DLX5) in the S-HuMSCs (P<0.05). Meanwhile, the enhanced osteogenic differentiation of HuMSCs was recovered by IL-32 overexpression (IL-32highHuMSCs) through activating the P38 signaling pathway, like as the S-HuMSCs (P<0.05). However, the osteogenic differentiation potential of IL-32highHuMSCs was significantly reversed by the P38 signaling pathway inhibitor SB203580 (P<0.05). Additionally, the HuMSCs, S-HuMSCs, and IL-32highHuMSCs all presented adipogenic-osteogenic differentiation potential, with higher levels of CD73, CD90, and CD105, and lower CD14, CD34, and CD45 (P>0.05). Furthermore, these findings were confirmed by the rat skull bone defect model, in which the cranial bone regeneration was more pronounced in the IL-32highHuMSCs treated group compared to those in the HuMSCs group, with higher expressions of RUNX2, ALP, BMP2, and DLX5 (P<0.05). Conclusion. We have confirmed that S-HuMSCs can enhance the osteogenesis and cranial bone regeneration through promoting IL-32-mediated P38 signaling pathway, which is proved that IL-32 may be a therapeutic target, or a biomarker for the treatment of cranial bone injuries.